Antihyperglycemic and Antiobesity Effects of JAL2 on db/db Mice. (16th March 2016) - Lee, In-Seung; Kim, Ki-Suk; Kim, Kang-Hoon; Park, Jiyoung; Jeong, Hyeon-soo; Kim, Yumi; Na, Yun-Cheol; Chung, Won Seok; Ahn, Kwang-Seok; Lee, Seok-Geun; Um, Jae Young; Lee, Jun Hee; et al.
Abstract : Lonicera japonica Thunb. (LJT) and Rehmannia glutinosa Libosch. (RGL) have been used traditionally as a herbal medicine in Korean medicine. Using LC/Q-TOF was performed to profile the two herbal medicines and the mixture of LJR and RGL (JAL2, ratio 1 : 1). We performed oral glucose tolerance test (OGTT) and plasma GLP-1 and insulin secretion by multiplex assays to investigate antidiabetic effects of LJT, RGL, and JAL2 in db/db mice, the mice model of type 2 diabetes mellitus (T2DM). Also, the antiobesity-related factors such as plasma peptide YY (PYY), triglyceride, total cholesterol, HDL, LDL, and weight of liver, epididymal, and retroperitoneal fat tissue were investigated. Through the multiplex assay, it was found that JAL2 treatment more efficiently attenuated high levels of blood glucose by stimulating GLP-1 secretion and reduced LDL concentration and weight of liver and retroperitoneal fat tissue compared to LJT or RGL treated separately. These results suggest that the JAL2 has antidiabetes and antiobesity effects in T2DM mice model.